(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background : Coronary Artery Disease (CAD) is one of the major causes of increased morbidity and mortality in developed and developing countries. Acute myocardial infarction is the most important consequence of coronary artery disease. Lipoprotein (a) is considered as a risk factor for acute myocardial infarction. The aim of the present study is to evaluate serum lipoprotein (a) level with acute myocardial infarction in different age group and to observe association of Lp (a) with diabetes mellitus in patients with AMI. Materials and methods : This was a hospital based cross-sectional study was conducted in the Department of Biochemistry & Cardiology of Chittagong Medical College Hospital from July 2018 to June 2019 with one hundred (100) patient with AMI and seventy (70) healthy people age ranging from 21 to 80 years. Results: Serum lipoprotein (a) level were significantly higher in patients with AMI (Cases) than that in healthy subjects (Controls) (40.47 ± 2.47mg/dl vs 20.42 ± 2.47mg/dl. The mean serum Lp (a) value was found increasing with age in patients with AMI (<40 year: 36.96 ± 7.93mg/dl, 40-60 year: 41.19 ± 3mg/dl and >60 year: 41.75 ± 4.95mg/dl. Conclusion: Serum Lp (a) level was significantly higher in patients with AMI. Serum Lp (a) level also increases with age, though the difference was not statistically significant. Estimation of serum Lp(a) level may project an early and important information for patients prior to acute MI. JCMCTA 2020 ; 31 (2) : 89-94